Alpha-Lipoic Acid Mediates Clearance of Iron Accumulation by Regulating Iron Metabolism in a Parkinson’s Disease Model Induced by 6-OHDA - Tai, Shengyan; Zheng, Qian; Zhai, Suzhen; Cai, Ting; Xu, Li; Yang, Lizhu; Jiao, Ling; Zhang, Chunlin (Frontiers in Neuroscience, 2020)
Disruption of neuronal iron homeostasis and oxidative stress are related to the pathogenesis of Parkinson’s disease (PD). Alpha-lipoic acid (ALA), a naturally occurring enzyme cofactor with antioxidant and iron chelator properties, has many known effects. It is known that ALA has neuroprotective effects on PD, but its underlying mechanism remains unclear. In the present study, we established PD models induced by 6-hydroxydopamine (6-OHDA) to explore the neuroprotective ability of ALA and its underlying mechanism in vivo and in vitro. Our results showed that ALA could provide significant protection from 6-OHDA-induced cell damage in vitro by decreasing the levels of intracellular reactive oxygen species and iron. Moreover, ALA significantly promoted the survival of the dopaminergic neuron in the 6-OHDA-induced PD rat model and remarkably ameliorates motor deficits by dramatically inhibiting the decrease of tyrosine hydroxylase expression and superoxide dismutase activity in the substantia nigra (SN). Interestingly, ALA attenuated 6-OHDA-induced iron accumulation both in the vivo and vitro by antagonizing 6-OHDA-induced up-regulation of iron regulatory protein 2 (IRP2) and divalent metal transporter 1 (DMT1). These results indicate that the neuroprotective mechanism of ALA against neurological injury induced by 6-OHDA may be related to the regulation of iron homeostasis and the reduced oxidative stress levels. Therefore, ALA may provide neuroprotective therapy for PD and other iron metabolism disorder related diseases.